THE PORTRAYAL OF AN AFGHAN WIFE IN NE SEIERSTADS THE BOOKSELLER OF KABUL: STYLISTIC ANALYSIS - Arina Isti'anah (Sanata Dharma University, 2018)
In the grammatical level of analysis, transitivity is one of the choices. The role of verb in a clause determines its process and participants, and thus imply particular meanings. This research took two chapters as the research data taken from a novel by ne Seierstad entitled The Bookseller of Kabul. Talking about literature about Afghanistan society, what attracts this research is the Afghan character named Sharifa. The research found that Seierstad employed various types of processes, participants and circumstances to describe Sharifa. First, the use of Actor and of material process aims at portraying the responsibility of an Afghan wife in spite of the sorrow seen from the mental process with Sharifa as the Senser. The use of relational process with Sharifa as the Carrier is to attach her to particular character, both physical and psychological states. In sum, the novel portrays the Afghan wife as a submissive, yet devoted character.